Towards an Effective Regulatory and Supervisory Framework for Latin America - Liliana Rojas-Suárez; Steven R. Weisbrod (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper raises fundamental questions about how banks in Latin America ought to be supervised. The concentration of wealth holders in Latin America and the equity markets` resulting illiquidity permit investors who control banks to subvert the intent of capital requirements, even when the bank itself is subject to rigorous accounting standards. A number of policy implications follow from the analysis. Three of policy recommendations derived from this analysis can be successfully implemented in the short run. Latin American supervisors should focus on: improving the markets that already work in Latin America, which currently are markets for bank liabilities; severely limiting public safety nets for bank liabilities so that risky banks face a high price for raising liabilities; and encouraging macroeconomic policies to play a much more important role in restraining bank risk in Latin America than in the industrial countries.
Keywords: 330